MENERAPKAN PEMBELAJARAN PENEMUAN DENGAN KINEMASTER UNTUK MENINGKATKAN PEMIKIRAN KRITIS SISWA - zega, Awin Krisdtiani; Laoli, Eka Septianti; Harefa, Yearning; Telaumbanua, Wahyutra Adilman (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
The inactivity of students at SMP Negeri 3 Gunungsitoli Alo’oa often creates a monotonous learning atmosphere. The students' lack of response to each learning material is also caused by the use of conventional learning models. This study aims to examine the implementation of the Discovery Learning model using the Kinemaster application in enhancing students' thinking skills. The benefit of this learning model is expected to enable students to think critically and respond to each stage of the learning process, thus contributing to the improvement of learning quality. The type of research used is Classroom Action Research (CAR), consisting of two implementation cycles, using a qualitative research method. The research subjects were 23 students of SMP Negeri 3 Gunungsitoli Alo’oa. The research instruments included observation sheets, documentation, and learning outcome tests. The results showed that the teacher's observation sheet scored 54% in the first cycle and 89.5% in the second cycle, while the students' critical thinking observation sheet scored 58.74% in the first cycle and 91.53% in the second cycle. Student learning outcomes in the first cycle reached 63.81% with a mastery percentage of 45%, and in the second cycle, the average reached 77.80% with a mastery percentage of 81.81%, categorized as very good. These results indicate that the Discovery Learning model using the Kinemaster application can improve students' critical thinking skills at UPTD SMP Negeri 3 Gunungsitoli Alo’oa.